2013 IEEE International Conference on Mechatronics and Automation 2013
DOI: 10.1109/icma.2013.6618150
|View full text |Cite
|
Sign up to set email alerts
|

New concept of in-water surface cleaning robot

Abstract: Abstract-This paper introduces a new concept of flexible crawling mechanism to design an industrial underwater cleaning robot, which is evaluated from the viewpoint of the capability to work underwater, scanning the desired surface, and bearing the reactions. This can be used as a robotic application in underwater surface cleaning and maintenance. We designed a robot that realizes the motion by contraction and extraction using DC-motors and vacuum technology. In this study we first focused on realizing the adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In suction systems, vacuum pressure is applied in sustaining adhesion to the structure. Vacuum is usually produced using suction engines, external hydraulic, plunger pump, centrifugal impeller, or passive suction cups [25]- [27] which create the negative pressure in the suction cup or chamber for wall-climbing. This can be applied to a variety of structures and materials (including non-ferromagnetic surfaces).…”
Section: Adhesion Mechanismmentioning
confidence: 99%
“…In suction systems, vacuum pressure is applied in sustaining adhesion to the structure. Vacuum is usually produced using suction engines, external hydraulic, plunger pump, centrifugal impeller, or passive suction cups [25]- [27] which create the negative pressure in the suction cup or chamber for wall-climbing. This can be applied to a variety of structures and materials (including non-ferromagnetic surfaces).…”
Section: Adhesion Mechanismmentioning
confidence: 99%
“…This robot, which is 1690 mm long, 554 mm wide, and 340 mm high, is an underactuated and deformable robot that solves the problem of moving on different surfaces of the hull (Souto et al 2013 , 2015 ). Albitar et al ( 2016 ) designed a crawling robot, as shown in Figure 14b , that is mainly composed of a moving mechanism, suction cups, and cleaning devices (Albitar et al 2013 , 2014 , 2016 ). NESSIE is an underwater hull cleaning robot that uses two circular rotating brushes, as shown in Figure 14c (Albitar et al 2016 ).…”
Section: Adhesion Technologies In Underwater Cleaning Robotsmentioning
confidence: 99%
“…The major drawback observed was, movement of the ship was not smooth and no control over the collection of garbage. In [6] introduced a new concept of flexibility crawling mechanism in designing an industrial underwater cleaning boat, which is capable of working underwater, scanning the desired surface, and recording biological reactions. The system design was limited to clean bio-fouled in water surfaces.…”
Section: IImentioning
confidence: 99%